An Overview of Vascular Dysfunction and Determinants: The Case of Children of African Ancestry - Matjuda, Edna N.; Engwa, Godwill Azeh; Sewani-Rusike, Constance R.; Nkeh-Chungag, Benedicta N. (Frontiers in Pediatrics, 2021)
The balance between dilatory and constrictive factors is important as it keeps blood vessels in a homeostatic state. However, altered physiological processes as a result of obesity, hypertension, oxidative stress, and other cardiovascular risk factors may lead to vascular damage, causing an imbalance of vasoactive factors. Over time, the sustained imbalance of these vasoactive factors may lead to vascular dysfunction, which can be assessed by non-invasive methods, such as flow-mediated dilation, pulse wave velocity, flow-mediated slowing, retinal vessel analysis, peripheral vascular reactivity, and carotid intima-media thickness assessment. Although there is increasing prevalence of cardiovascular risk factors (obesity and hypertension) in children in sub-Saharan Africa, little is known about how this may affect vascular function. This review focuses on vasoactive factors implicated in vascular (dys)function, highlighting the determinants and consequences of vascular dysfunction. It further describes the non-invasive methods used for vascular (dys)function assessments and, last, describes the impact of cardiovascular risk factors on vascular dysfunction in children of African ancestry.